2021
DOI: 10.1080/19476337.2021.1971771
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical, cytotoxic, and genotoxic evaluation of protein extract of Amaranthus hypochondriacus seeds

Abstract: Amaranth has been of interest for its nutritional quality and its multiple benefits; however, there is little research on its toxicological effect. This work studied antinutritional compounds, the cytotoxic and genotoxic effect in the Amaranthus protein extract (PEAh). The content of lectins, tannins, saponins, and trypsin inhibitors was determined. Biological studies were conducted to determine toxicity in male CD-1 mice by intraperitoneal administration. The genotoxic potential was determined by the micronuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Presence of anti-nutritional compounds in treated and untreated seeds of several amaranth species has been reported in extant literature, as processing affects the content of some of these compounds [ 8 , 9 ]. In the present study, anti-nutritional compounds were found in all five amaranth seed samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Presence of anti-nutritional compounds in treated and untreated seeds of several amaranth species has been reported in extant literature, as processing affects the content of some of these compounds [ 8 , 9 ]. In the present study, anti-nutritional compounds were found in all five amaranth seed samples.…”
Section: Discussionmentioning
confidence: 99%
“…The findings reported by Valadez-Vega, further indicate that Amaranthus hypochondriacus species have high concentrations of lectins and trypsin inhibitors and lower concentrations of tannins and saponins [ 8 ]. The findings reported by Valadez-Vega, further indicate that Amaranthus hypochondriacus species have high concentrations of lectins and trypsin inhibitors and lower concentrations of tannins and saponins [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The purification results were further utilized in this work for determining protein sizes by NATIVE-PAGE and SDS-PAGE methods, given that several Phaseolus lectins are composed of four subunits [ 35 , 36 ]. Available data further indicate that the MW of Phaseolus vulgaris lectin subunits can vary between 30 and 36.5 kDa [ 6 , 9 , 24 , 25 , 37 ], concurring with the values obtained for LBBV and LBBS using SDS-PAGE.…”
Section: Discussionmentioning
confidence: 99%